IDENTIFIKASI DAN ISOLASI SENYAWA LIKOPEN DARI SEMANGKA (CITRULLUS LANATUS) - Eva Monica; Rollando Rollando (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACTLycopene is one of the phytochemical compounds of the carotenoid group, the main producer of red pigments found in watermelons. Watermelon is a round-shaped vines containing vitamin C and vitamin A and has high antioxidant levels. This study aims to identify lycopene compounds in watermelons. Extraction of watermelon flesh by maceration method. Identification of lycopene compounds with UV-Visibel spectrophotometry instrument followed by identification with the TLC method and fractionation of extracts using preparative TLC with chloroform: ethanol (1: 1) solvents, and identification of fractionation results with Fourier Transform Infrared Spectroscopy (FT-IR). The results of the identification of watermelon fruit extract using the TLC method obtained three spots and the results of UV-Vis spectrophotometry showed three peaks namely between 440-520 nm. The identification of fractionation of watermelon extract using FT-IR obtained a constituent group of lycopene structures, but did not show the R-CH = CH-R group that is owned by lycopene, whereas the results of the test with UV-Vis spectrophotometry appearing at 206 and 245 which indicate the presence of other compounds. From the results of the study it can be concluded that the testing of known extracts of watermelon fruit contains lycopene compounds, but the testing of lycopene identification on the results of fractionation of watermelon fruit extracts was not found with certainty the existence of lycopene because the FT-IR results were only shown and contained on the results UV-Vis spectrophotometry was found to be the wavelength of other compounds.keywords: Watermelon, Lycopene, UV-Vis Spectrophotometry, IR Spectrophotometry